Nouvelle professionnalité des enseignants d’éducation physique et sportive en lycée professionnel. Bonne distance, séquençage et extériorisation des règles du travail scolaire - Sabine Coste (Recherches en Éducation)
The vocational school is a teaching changing space. Teachers live reforms that challenge the business including the renovation of the certification. Our research focuses on a group of teachers, physical education and sports teachers who have to implement new forms of certification. We study the teacher professionalism through a comparative approach of two groups of professors, teachers already practicing and teachers entering the profession and discovering a learning environment to which they paid little attention during their initial training. Reform of the interim course evaluation, requiring the construction of a new device evaluation and new scoring rules, has become for us a lever to access to the work of teachers. Our analysis allowed us to highlight revealing elements of a "new job” mobilized by teachers entering the profession, the most significants are presented in this article. Thus the construction of the "right distance", strengthening the sequencing and externalizing rules schoolwork characterizes how to work as "new teachers" to teach with students who are relearning academic standards.